Therapies and delivery systems for diabetic wound care: current insights and future directions - Yadav, Preeti Singh; Singh, Mahendra; Vinayagam, Ramachandran; Shukla, Prashant (Frontiers in Pharmacology, 2025)
The global rise in diabetes mellitus has been paralleled by an increase in associated complications, notably impaired Wound Healing. Non-healing diabetic wounds are driven by multifactorial pathogenesis involving hyperglycemia, immune dysfunction, impaired angiogenesis, bacterial infections, and increased oxidative stress. Traditionally, a variety of plant-derived extracts and phytochemicals such as quercetin, curcumin, and paeoniflorin have been employed in the treatment of diabetic wounds worldwide. These agents exert their therapeutic effects primarily through antioxidant, antibacterial, anti-inflammatory, and pro-angiogenic mechanisms and properties, typically with minimal side effects. Recent advancements have highlighted the potential of integrating phytoconstituents with metal nanoparticles to enhance Wound Healing efficacy. Nanoformulations improve targeted phytochemical delivery and offer synergistic benefits due to intrinsic antimicrobial and antioxidant properties, enhanced antioxidant activity, and high biocompatibility. Similarly, polymeric nanocarrier-based delivery systems have emerged as a promising strategy to address the limitations of conventional wound treatments, promoting faster and more efficient healing in diabetic patients. This review comprehensively discusses the pathophysiology and clinical challenges associated with diabetic Wound Healing, explores the therapeutic potential of key phytochemicals, and presents the current progress in nanoparticle-based delivery systems (metallic and polymeric) for diabetic wound management. Additionally, it provides an update on recent patents and clinical trials involving phytoconstituents and their formulations for the treatment of diabetic wounds.